2009
DOI: 10.1111/j.1420-9101.2009.01772.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, growth and the evolution of sexual size dimorphism

Abstract: The integration of macroevolutionary pattern with developmental mechanism presents an outstanding challenge for studies of phenotypic evolution. Here, we use a combination of experimental and comparative data to test whether evolutionary shifts in the direction of sexual size dimorphism (SSD) correspond to underlying changes in the endocrine regulation of growth. First, we combine captive breeding studies with mark‐recapture data to show that male‐biased SSD develops in the brown anole lizard (Anolis sagrei) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
105
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 75 publications
8
105
0
1
Order By: Relevance
“…The Journal of Experimental Biology 216 (10) et al (Cox et al, 2009) and other resources not included in their study (Civantos, 2002;Duncan, 2011;Kubička et al, 2013), we conclude that the support for the hypothesis that gonadal androgens directly influence the endocrine growth axis in squamate reptiles is not very strong. We suggest that previously reported effects of gonadal androgens on growth in male lizards could be attributed either to unnatural levels of testosterone, or to indirect consequences of altered behaviour or social status in manipulated individuals (see also Cox et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The Journal of Experimental Biology 216 (10) et al (Cox et al, 2009) and other resources not included in their study (Civantos, 2002;Duncan, 2011;Kubička et al, 2013), we conclude that the support for the hypothesis that gonadal androgens directly influence the endocrine growth axis in squamate reptiles is not very strong. We suggest that previously reported effects of gonadal androgens on growth in male lizards could be attributed either to unnatural levels of testosterone, or to indirect consequences of altered behaviour or social status in manipulated individuals (see also Cox et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…In their review, Cox and colleagues (their table2) concluded that regardless of phylogenetic distribution, androgens enhance male growth in male-larger species, inhibit it in female-larger species, but have ambiguous or no obvious effect in species that are monomorphic in body size (Cox et al, 2009). They speculated that this bipotential effect of testosterone on growth could involve direct effects on the endocrine growth axis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we suggest that adult males may live longer than adult females, since reptiles generally show indeterminate growth. If so, the longer lifespan in males might have a genetic basis (Badyaev 2002, Cox et al 2009, Barret and Richardson 2011 since males do not defend territories or females, and do not engage in agonistic behavior against male conspecifics (Fox and Shipman 2003, ESB pers. observ.…”
Section: Discussionmentioning
confidence: 99%